"Current Approaches to Organizing Distance Learning in The Field of Electrical Engineering" (Eurasian Research Bulletin, 2024)
The indispensability of incorporating distance learning technologies in organizing the educational process in the field of electrical engineering is emphasized in the article. Nowadays, to meet the demands of the labor market and to enhance the quality of training engineering professionals, it is crucial to integrate digital technologies into the educational process. The recommended technology proposed is in the form of mobile applications, which can be utilized by students studying in both traditional and online formats in all undergraduate education directions related to the technical field, as well as by staff members of all sectors of production and service provision, and by both professional and higher education professors and instructors. Additionally, effective solutions for teaching the subject "Electrical Engineering and Electronics" to students at Tashkent State Technical University have been recommended based on the results of trials conducted, which have proven to be highly efficient. Furthermore, the results of pedagogical experimentation conducted during scientific research are announced.